Human-centered systems analysis of mixed equipage in ocean air traffic control - Major, Laura M. (Laura Mary), 1980- (Massachusetts Institute of Technology, 2005)
Thesis (S.M.)--Massachusetts Institute of Technology, Dept. of Aeronautics and Astronautics, 2005. Includes bibliographical references (p. 107-110). Technical capabilities for improved communication, surveillance, and navigation (CNS) over the oceans are currently available. However, all aircraft operators will not equip simultaneously because of the high costs required. Consequently, as these CNS systems are integrated into oceanic air transportation architecture, the controller will have to manage the current low frequency surveillance and communication paths in parallel with future enhanced CNS. The cognitive effects of the mixed equipage environment were studied through field studies and experimental analysis. Field studies at New York Center, Oakland Center, and Reykjavik Center in Iceland were conducted to identify human-centered systems issues with the emerging mixed equipage environment. Findings show that the integration of varying communication latencies influences controller planning. The fusion of multiple surveillance sources and the application of varying separation standards based on equipage was found to limit the cognitive processes of the controller. These limitations may constrain the controller from providing full efficiency benefits to aircraft equipped with the highest capabilities, which would reduce the incentives for equipping. Experimental analysis was conducted to further study the integration of high and low frequency surveillance and the use of varying separation standards. Results show that workload increases and situation awareness degrades in the mixed surveillance environment, compared to segregated operations. The results also demonstrate that efficiency benefits attained by equipped aircraft are in fact limited in the mixed equipage environment. Implications for the design of air traffic control systems and procedures are also discussed. (cont.) Strategies for the segregation of airspace based on equipage are suggested to alleviate controller cognitive limitations and ...